Central sensitisation in pelvic pain: A cohort study. (11th August 2022) - Ryan, Amelia; Healey, Martin; Cheng, Claudia; Dior, Uri; Reddington, Charlotte
Abstract : Background: Central sensitisation (CS) leads to pain amplification and impacts on the management of pelvic pain (PP). Identification of CS in patients with PP may provide additional treatment pathways and improve patient outcomes. Aims: The aims are to quantify the prevalence of questionnaire‐predicted CS (QPCS) in patients presenting with PP and investigate associations between QPCS and clinical variables. Materials and methods: This was an observational, cross‐sectional study. Subjects with PP completed a questionnaire comprising four validated tools: the Central Sensitisation Inventory (CSI) for QPCS, Pain Catastrophising Scale for Catastrophising Trait, Bladder Pain/Interstitial Cystitis Symptom Score for bladder pain syndrome (BPS) and the Rome IV criteria for irritable bowel syndrome (IBS). Results: One hundred and eleven women were enrolled in the study; 74.8% ( n = 83) had a CSI score of >40, indicating the presence of QPCS. Subjects with QPCS were more likely to screen positive for catastrophising trait (odds ratio (OR) 3.57, 95% CI 1.19–10.76, P = 0.02), BPS (OR 11.77, 95% CI 2.13–64.89, P = 0.005) and IBS (OR 2.6, 95% CI 1.05–6.43, P = 0.04). They were more likely to experience pain for more than two years (OR 4.98, 95% CI 1.94–12.82, P = 0.001) and other pain symptoms involving bladder (OR 9.87, 95% CI 2.52–38.67, P = 0.001), bowel (OR 3.13, 95% CI 1.31–7.48, P = 0.01), back (OR 4.17, 95% CI 1.66–10.51, P = 0.002) and vulva (OR 3.61, 95% CI 1.21–10.82, P = 0.02). They also had higher previous diagnoses of mental health disorder (OR 3.5, 95% CI 1.5–8.4, P = 0.005) or IBS (OR 8.9, 95% CI 1.6–49.1, P = 0.01). Conclusions: QPCS occurs frequently in patients with PP, and subjects with QPCS experience more prolonged and complex pain.